2011
DOI: 10.3168/jds.2010-3439
|View full text |Cite
|
Sign up to set email alerts
|

Cow-level and herd-level risk factors for subclinical endometritis in lactating Holstein cows

Abstract: The objectives of this study were to obtain prevalence estimates for subclinical endometritis (SCE), determine cow- and herd-level risk factors, and evaluate the reproductive consequences of SCE. A cross-sectional study was used to determine prevalence and risk factors with cows followed in a prospective study to determine reproductive outcomes. Lactating Holstein cows were sampled between 40 and 60 d in milk using low-volume uterine lavage, and cytology was evaluated to determine SCE status. In total, 779 cow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
123
11
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(160 citation statements)
references
References 21 publications
18
123
11
8
Order By: Relevance
“…The prevalence of estruses accompanied by cloudy vaginal mucus did not differ between cows with one or multiple lactations, which is not totally in line with data of Cheong et al (2011), who found that primiparous cows producing more milk were at higher risk of subclinical endometritis, whereas multiparous cows producing more milk had lower risk of this reproductive disorder. Potter et al (2010) also found that primiparous cows had higher risk of presenting clinical endometritis.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The prevalence of estruses accompanied by cloudy vaginal mucus did not differ between cows with one or multiple lactations, which is not totally in line with data of Cheong et al (2011), who found that primiparous cows producing more milk were at higher risk of subclinical endometritis, whereas multiparous cows producing more milk had lower risk of this reproductive disorder. Potter et al (2010) also found that primiparous cows had higher risk of presenting clinical endometritis.…”
Section: Resultssupporting
confidence: 74%
“…The prevalence of cloudy vaginal mucus at AI (21.4%) was very close to that found for uterine infections based on endometrial cytology, 4 to 8 weeks postpartum (Potter et al, 2010;Cheong et al, 2011;Baranski et al, 2012;Lima et al, 2013). The prevalence of estruses with cloudy vaginal mucus in the present study was lower than some of the incidence rates previously reported for uterine infectionscytologically-diagnosed endometritis or vaginal purulent discharges (LeBlanc et al, 2002;Gilbert et al, 2005;Hendricks et al, 2006) -and higher than others observed by clinical examination and uterine cytology (Knutti et al, 2000;Green et al, 2011).…”
Section: Resultscontrasting
confidence: 55%
“…Clinical and subclinical endometritis negatively affect the performance of the world's dairy industry; economic losses are related to delay in the resumption of ovarian activity, increased number of services per conception, decreased milk yield, and costs of treatment of the disease (6,7). The United States and Europe have 8.5 and 24.1 million dairy cows and uterine infection costs 650 million dollars and 1.4 billion Euros, respectively (2).…”
Section: Introductionmentioning
confidence: 99%
“…Of the 3 components of the disease triangle, there is good evidence for the susceptibility of the host and for the role of pathogenic bacteria. There is less evidence for the effect of the environment (4), although it cannot be disregarded (14). Therefore, this review will focus on the effect of systemic and cellular indicators of energy balance on immune function and the effect of calcium status on immune function and susceptibility to uterine diseases, the mechanism of recognition of pathogens by professional phagocytes, the uterine endometrium and granulosal cells, the main pathogens that cause uterine disease, and the immune response to pathogens by the uterine endometrium and professional phagocytes.…”
Section: Introductionmentioning
confidence: 99%